Foul play is associated with injury incidence: an epidemiological study of three FIFA World Cups (2002–2010). Issue 15 (28th August 2013) - Ryynänen, Jaakko; Junge, Astrid; Dvorak, Jiri; Peterson, Lars; Kautiainen, Hannu; Karlsson, Jón; Börjesson, Mats
Abstract : Background: Foul play has been considered as one of the most important known extrinsic risk factors for injuries in football. Aims: To compare the incidence and characteristics of foul play injuries and non-foul injuries. Methods: Team physicians' postmatch injury reports and official match statistics were obtained from all matches of the 2002, 2006 and 2010 Fédération Internationale de Football Association World Cups. Results: The number of injuries was associated with the number of fouls in a match. The incidence of foul play injuries (20.6/1000 match-hours, 95% CI 17.3 to 24.4) was significantly lower than that of non-foul injuries (42.6, 37.7 to 47.9), which also applied to all playing positions. The causation of injury (foul/non-foul), match period and teams' drawing/losing/winning status were associated with the injury incidence. The interactions between the causation of injury (foul/non-foul) and match time, as well as the teams' drawing/losing/winning status or playing position were not statistically significant. The median (IQR) days of absence resulting from foul play injuries were significantly shorter than that of non-foul injuries. The lower leg and ankle were more common locations for foul play injuries than for non-foul injuries, whereas the opposite was observed for thigh injuries. Contusions were a more common type of foul play injuries than non-foul injuries, while the opposite was found for muscle strains/ruptures/tears. Conclusions: The numbers of injuries and fouls in a match were significantly associated. No significant differences in the variation of foul play and non-foul injury incidences regarding match period, teams' current winning/drawing/losing status and playing position were observed, suggesting that foul play injuries and non-foul injuries may share similar underlying risk factors.